INTEGRATION OF INFORMATION SYSTEMS IN AN EFFORT TO IMPROVE FINANCIAL AND HUMAN RESOURCE MANAGEMENT PERFORMANCE at PT SENTRA FOOD INDONESIA Tbk - Miftah Reza Tama Faturohman; Yonartilia Mamis; Hadi Supratikta (PT. Jurnal Center Indonesia Publisher, 2024)
This study investigates the role of information systems integration in improving the performance of financial management and human resources (HR) at PT Sentra Food Indonesia Tbk. Through Literature Research, this research details the information system integration strategy implemented by the company and its impact on financial and HR management. The results show that effective information system integration enables better access to financial information, supports more timely decision making, and improves the company's operational efficiency. In addition, information system integration also contributes to HR management processes, including recruitment, training, and employee performance evaluation. The findings highlight the importance of investment in information technology and HR development as strategies to improve overall company performance. The practical implications of this study provide valuable insights for company management in designing integrated strategies to achieve their business goals.